2016
DOI: 10.1038/srep27071
|View full text |Cite
|
Sign up to set email alerts
|

Stellettin B Induces G1 Arrest, Apoptosis and Autophagy in Human Non-small Cell Lung Cancer A549 Cells via Blocking PI3K/Akt/mTOR Pathway

Abstract: Until now, there is not yet antitumor drug with dramatically improved efficacy on non-small cell lung cancer (NSCLC). Marine organisms are rich source of novel compounds with various activities. We isolated stellettin B (Stel B) from marine sponge Jaspis stellifera, and demonstrated that it induced G1 arrest, apoptosis and autophagy at low concentrations in human NSCLC A549 cells. G1 arrest by Stel B might be attributed to the reduction of cyclin D1 and enhancement of p27 expression. The apoptosis induction mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
120
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 38 publications
7
120
0
Order By: Relevance
“…Even more interesting is that the PI3K/AKT signaling pathway cause drug resistance by mediating tumor cells escape from apoptosis. 37, 38 Given the critical role of the PI3K/AKT signaling pathway in tumor cell drug resistance, we investigated whether ASIC1a mediated calcium influx to regulate the PI3K/AKT signaling pathway. Western blot analysis showed that the levels of PI3K and the phosphorylation of AKT were decreased in Bel7402/FU and HepG2/ADM cells treated with ASIC1a shRNA (Figure 8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even more interesting is that the PI3K/AKT signaling pathway cause drug resistance by mediating tumor cells escape from apoptosis. 37, 38 Given the critical role of the PI3K/AKT signaling pathway in tumor cell drug resistance, we investigated whether ASIC1a mediated calcium influx to regulate the PI3K/AKT signaling pathway. Western blot analysis showed that the levels of PI3K and the phosphorylation of AKT were decreased in Bel7402/FU and HepG2/ADM cells treated with ASIC1a shRNA (Figure 8).…”
Section: Resultsmentioning
confidence: 99%
“…33, 34, 35, 36 As is known to all, PI3K/AKT pathway caused drug resistance, through which mediated tumor cells escape apoptosis. 37, 38 In cancer cells, whether Ca 2+ involved in drug resistance via the regulation of PI3K/AKT pathway is still unknown.…”
mentioning
confidence: 99%
“…To analyse autophagic flux, LX‐2 cells were transfected with a tandem fluorescent mRFP‐GFP‐tagged LC3 plasmid 24 using Lipofectamine 2000. The expression of GFP and mRFP was visualized with Olympus FV1000 laser scanning confocal microscope (Olympus, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…63 Briefly, treated cells were harvested, washed with PBS, and stained with 20  μ M DCFH-DA (Applygen Technologies, Beijing, China) for 20 min at 37 °C in the dark. Fluorescent signals were detected with a FACS Verse flow cytometer (BD, Germany).…”
Section: Methodsmentioning
confidence: 99%